The clinical implication of CD45RA+ naïve T cells and CD45RO+ memory T cells in advanced pancreatic cancer: a proxy for tumor biology and outcome prediction - Junjie Hang; Junjie Huang; Siyuan Zhou; Lixia Wu; Yingwei Zhu; Lina Zhu; Hanyu Zhou; Kequn Xu; Hua Jiang; Xuguang Yang (Cancer Medicine)
Abstract Naïve and memory T cells play a pivotal role in solid tumor pathogenesis but their role in pancreatic cancer progression remains elusive. Thus, we aimed to investigate their clinical potential in advanced pancreatic cancer (APC). Flow cytometry was performed to evaluate the level of baseline peripheral naïve and memory T cells from 137 APC patients before receiving first‐line chemotherapy. Interrelationships between naïve, memory T cells and clinicopathological variables were evaluated using Pearson’s correlation. The prognostic impact of naïve and memory T cells were assessed by Kaplan‐Meier analysis and Cox regression. The correlation between naïve/memory T cells and tumor progression was investigated by Student’s t test. CD4+ naïve/memory ratio showed close correlations with hemoglobin, red blood cell (RBC), absolute neutrophil count (ANC) and platelet while CD8+ naïve/memory ratio was correlated with hemoglobin, RBC and CEA. Higher baseline lever of CD4+CD45RO+/CD4+ was correlated with better overall survival (OS) (P = 0.036). Patients with CD4+ naïve/memory ratio ≥0.36 had a poorer OS than those with CD4+ naïve/memory ratio <0.36 (P = 0.021). In addition, CD4+ naïve/memory ratio showed independent prognostic impact (HR 1.427, 95% CI 1.033‐1.973, P = 0.031). Furthermore, poorer clinical response was correlated with higher level of CD8+ naïve/memory ratio after the third cycle of chemotherapy (P = 0.01). Besides, patients with a lower level of CD8+ naïve/memory ratio had longer progression‐free survival (PFS) (P = 0.028). We propose CD4+ naïve/memory ratio as a novel prognostic biomarker for APC. In addition, CD8+ naïve/memory ratio can be a candidate marker for predicting PFS and the change of its level may reflect the progression of APC.